Enhancing Electrical Power Engineering Education in North Sumatra: Evaluating the Effectiveness and Practicality of Consortium Collaborations Between Academia and Industry - Junaidi, Agus; Afandi, Marwan; Pangaribuan, Wanapri; K, Abd Hamid; Rahmaniar, Rahmaniar (STAI Hubbulwathan Duri, 2024)
Simulation technology tools are becoming important learning tools in higher education, facilitating the development of practical and cognitive skills in a safe and widely accessible environment. Simulation technology is applied in practicing and developing practical learning skills in a safe environment, without real risks. Computers as media and are used to improve learning outcomes and facilitate students in innovative learning. The importance of using simulation media in learning electricity engineering because inviting students to learn and interact with simulations can improve critical thinking skills, problem solving, and decision making. The simulation media was developed using the ADDIE model to achieve learning effectiveness targets by observing the parameters of alignment between simulation content and learning outcomes, interactivity that allows students to be actively involved in the learning process, the quality of feedback provided by simulations to help students understand in improving learning outcomes in the field of electricity engineering. The results of testing 21 respondents showed an increase in student involvement and motivation in the pretest results of 65.5 and post-test 83.38 in the experimental class, indicating that there was an increase in learning outcomes from media users. Practicality test 80% in the practical category shows the implication of using the media provides convenience.